Bluetooth-based location aware for mobile application / Ahmad Suhail Qamil Pahmin - Pahmin, Ahmad Suhail Qamil (2017)
Indoor positioning has become very highly demanded and increasing in popularity to promotes a high-quality information based on user location in indoor environments. An indoor positioning application allows user to moves around in an indoor environment while getting information based on their current location. It improves the user experience in a whole new level leading to a productive industry. However, most researches conducted focused on outdoor positioning and the weakness of outdoor positioning is that the signal weakens when it penetrates into buildings producing an inaccurate output to the user. There were several researches that have been conducted on indoor positioning such as Wi-Fi, Bluetooth, QR Code, RFID, Infrared, and BLE. Nevertheless, these works only focus on one technology leading to a less precise indoor positioning measurement. Yet, works related to indoor positioning are still lacking and is still highly demanded by the industry. This is to improve the effectiveness of indoor positioning. As a result, this project proposed a hybrid of Wi-Fi and BLE Indoor Positioning Location Awareness for Mobile Application. This application allows users to gain accurate and immediate information during their experience in an indoor environment. Results produced from the analysis proved that this project application provides accurate readings and information. In conclusion, the Bluetooth-Based Location Aware for Mobile Application can greatly provide a quality information proving the concept of indoor positioning location awareness.